2008
DOI: 10.1177/1545968308317752
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestment and Movement Disruption Following Stroke

Abstract: The association between functional impairment, propensity for reinvestment, and time spent in rehabilitation indicates that exclusive reliance on conscious motor processing strategies in the rehabilitation setting may be an impediment to regaining functional independence. There is a need to develop motor learning strategies for rehabilitation that restrain the propensity for reinvestment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 36 publications
7
72
0
5
Order By: Relevance
“…The level of self-reported conscious processing was assessed after each pressure condition using a putting specific version (Cooke, Kavussanu, McIntyre, Boardley, & Ring, 2011;Vine et al, 2013) of the conscious motor processing subscale of the Movement Specific Reinvestment Scale (Orrell, Masters, & Eves, 2009). Participants were asked to indicate how they felt while putting in relation to six items, including, "I thought about bad putts" and "I tried to figure out why I missed putts".…”
Section: Methodsmentioning
confidence: 99%
“…The level of self-reported conscious processing was assessed after each pressure condition using a putting specific version (Cooke, Kavussanu, McIntyre, Boardley, & Ring, 2011;Vine et al, 2013) of the conscious motor processing subscale of the Movement Specific Reinvestment Scale (Orrell, Masters, & Eves, 2009). Participants were asked to indicate how they felt while putting in relation to six items, including, "I thought about bad putts" and "I tried to figure out why I missed putts".…”
Section: Methodsmentioning
confidence: 99%
“…7,8,11 In this study, a mean difference in Conscious Motor Processing subscale scores of only 3.3 units was observed between those with or without knee pain; however, this would increase the likelihood of knee pain by approximately 50%. Moreover, the difference in mean scores between those without knee pain and those with knee pain due to sudden injury was nearly 6 units, notwithstanding that the sample size was small and the confidence intervals consistent with a much smaller increase.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have also found that propensity for conscious motor processing plays a more prominent role than movement self-consciousness in people with movement related problems, such as falling, 7 stroke, 8 and Parkinson's disease. 11 These findings suggest that concerns about moving effectively (or safely), which are likely to involve conscious motor processing, outweigh concerns about making a good impression when moving, which are likely to involve movement self-consciousness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People after stroke have shown to have greater propensity to reinvestment compared to the age-matched, non-disabled population 49 . Within the current study an adapted version of the MSRS specifically to gait is used.…”
Section: Movement Specific Reinvestment Scale Adapted For Gait (Msrs)mentioning
confidence: 99%